تفعيل المشاركة المجتمعية لتحقيق رضا الزوار بالمتاحف: متحف الآثار بمكتبة الإسكندرية: دراسة حالة - راشد، محمد جمال; عمر، إيمان صلاح (الإتحاد العام للآثاريين العرب, 2024)
تلعب المتاحف دورًا ملموسًا في خدمة المجتمع عبر عدة محاور بغية تلبية الاحتياجات والاهتمامات للزوار والمجتمع عامة، ويُعدُّ رضا الزائر غاية رئيسة يسعى المتحف لتحقيقها، وهي غاية لا تدرك إلا بإشراك المجتمع (الزوار) في ترسيم رسالة المتحف، أهدافه، وأولوياته، وفي تقييم ما يقدمه من فعاليات وأنشطة، تعد المشاركة المجتمعية إحدى الركائز الفعالة في بناء علاقة وطيدة فيما بين المتحف والمجتمع، وتعضيد صلته بالمتحف وأنشطته، ومن ثم الوصول لرضا الزائر. لذا تهدف هذه الورقة لإبراز أهمية المشاركة المجتمعية في بناء قنوات اتصال بين المتاحف والمجتمع، والتأكيد على دورها في رفع الوعي المجتمعي، وتعظيم دور المتحف الخدمي، وصولاً لتحقيق رضا الزوار من مختلف الشرائح والفئات الاجتماعية والثقافية؛ وذلك عبر تقديم خطة للمشاركة المجتمعية، وتفعيل آليات الوصول لشرائح المجتمع المختلفة، وإبراز دور المشاركة المجتمعية في التنمية المستدامة، لقد تم اختيار متحف الآثار بمكتبة الإسكندرية نموذجا لتطبيق هذه الدراسة على دور المتحف وتحليل المجتمع المحيط بالمتحف في سبيل تحقيق مشاركة مجتمعية فعالة كخطوة رئيسة تسهم في الوصول الرضا الزائر وتحقيق المتحف لمعايير الجودة الشاملة. Museums serve society on several axes to meet the needs and interests of visitors and communities in general. Visitor satisfaction is a major goal, which the museum always strives for. A goal that can be realized by involving the community in defining the museum's mission, goals, and priorities, and in evaluating the activities it offers. Community participation is one of the most effective pillars of building a strong relationship between the museum and the community. Thus, museums should sustain such relationship through strengthening their activities, which ultimately results in the visitors’ satisfaction. Therefore, this paper aims to highlight the importance of community participation in building bridges between the museum and society. It also emphasizes its role in raising community awareness and maximizing museum service. This is to ensure visitors' satisfaction. This is done by presenting a plan for community participation. It also activates mechanisms to reach different segments of society and highlighting the role of community participation in sustainable development. The Museum of Antiquities in the Bibliotheca Alexandrina was chosen for applying this study to the role of the museum and analyzing the community surrounding the museum in order to achieve effective community participation as a major step that contributes to visitor satisfaction and the museum's achievement of comprehensive quality standards.
Keywords: المؤسسات الثقافية -- التوعية المجتمعية -- التفاعل المجتمعي -- المتاحف المصرية